Enhancing Early Reading Skills Through Syllable Card Media: A Quasi-Experimental Study Among First-Grade Elementary Students in Indonesia - Putri Mardhotillah; Habudin Habudin; Juhji Juhji (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2026)
Early reading skills are very important for elementary school students' future academic success, but many struggle to learn to read and become fluent. Reading science-based learning methods stresses structured phonological learning to help kids learn to read early on. The objective of this study was to evaluate the efficacy of syllable flashcards in enhancing early reading skills among first-grade elementary school students. We used a quantitative quasi-experimental design with a non-equivalent control group. There were 62 students at Lemah Abang Public Elementary School in Kasemen District, Serang City, Indonesia. The experimental group was taught using syllable flashcards, while the control group learned in the usual way, using textbooks. We gathered data by administering a pre-test and a post-test that measured six aspects of students' early reading skills. Statistical analysis using paired and independent-samples t-tests indicated a significant improvement in students' reading performance post-intervention (p < 0.05). The experimental group exhibited significantly elevated post-test scores, characterized by substantial within-group and moderate between-group effect sizes, signifying a significant educational impact. These results show that syllable card media can improve phonological decoding and support steady early reading development. This has practical implications for evidence-based literacy teaching and for elementary school practices aligned with SDG 4: Quality Education.